(untitled) (Paliativní medicína, 2024)
A review article mapping the possible links and interdisciplinary collaboration between pediatric palliative care and child and adolescent psychiatry. It presents an overview of the published articles regarding this topic, the potential benefits for patients and their families, a description of the main psychiatric symptoms and disorders commonly encountered in pediatric palliative care and the potential contribution of the child psychiatrist to an integrated and holistic approach to complex cases.